2020
DOI: 10.1371/journal.pone.0237255
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of hemoglobin detergency by probability density functional method

Abstract: In this study, washing tests were performed using samples prepared by contaminating fabrics with hemoglobin, and a kinetic analysis was conducted based the probability density functional method, which expresses the cleaning power using two parameters σ rl (related to the cleaning mechanism) and μ rl (related to the level of cleaning power). This method allows for the processing of uncertainties specific to protein washing under the assumption that the soil adhesion and detergency are in accordance with a norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Then, the calculated values of Δ X + Δ Y and the experimental value Δ( X + Y ) were compared (Table 2). As a result of comparing the calculated values and the experimental values for all combinations of the two conditions, which was improved method from the previous reports (Oya et al, 2020; Oya‐Hasegawa et al, 2021), it was found that Δ X + Δ Y and Δ( X + Y ) were almost close. Therefore, an addition law was observed between the pH and the stirring effect, and it was judged that the interaction between the two cleaning elements was an additive effect.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Then, the calculated values of Δ X + Δ Y and the experimental value Δ( X + Y ) were compared (Table 2). As a result of comparing the calculated values and the experimental values for all combinations of the two conditions, which was improved method from the previous reports (Oya et al, 2020; Oya‐Hasegawa et al, 2021), it was found that Δ X + Δ Y and Δ( X + Y ) were almost close. Therefore, an addition law was observed between the pH and the stirring effect, and it was judged that the interaction between the two cleaning elements was an additive effect.…”
Section: Resultsmentioning
confidence: 81%
“…It has been demonstrated that the parameter σ rl is related to the type of dirt and the dirt removal mechanism (Fujimoto et al, 2017; Oya, 2019). Whereas, μ rl was used to determine the interaction between two different cleaning elements, and additive effect for protein soil (Oya et al, 2020) and synergistic effect for fatty acid soil (Oya‐Hasegawa et al, 2021), were observed with respect to temperature and pH effects. Although an additive effect between pH and agitation was estimated for fatty acid soil, sufficient data have not been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…During simulation, all frames were employed to study the molecular behavior of HSA. Finally, generated trajectory files were analyzed for examination of structural characteristics of HSA in terms of root‐mean‐square deviation (RMSD), 58 root‐mean‐square fluctuation (RMSF), 59 solvent accessible surface area (SASA), 60 the radius of gyration (Rg), 61 FEL, 62 PCA, 63 and PDF 64 …”
Section: Methodsmentioning
confidence: 99%
“…To rigorously investigate the impact of the N501Y mutation on the folding characteristics of spike protein, structural alignment along with three functions including the probability density function (PDF), 46 contact map, 47 and tunnel analysis 48 were applied for the residues around the mutated position. PDF was examined based on dihedral angle and triangle area using G_Measure (v.0.8); in addition, contact maps for carbon alpha and tunnel analysis were analyzed by utilizing Pymod (v3.0) and Caver (3.0.3), respectively.…”
Section: Tertiary Structure Topology Analysismentioning
confidence: 99%